POSTPANDEMIC ECONOMIC RECOVERY: ANALYSIS OF INCOME TAX COLLECTION IN MYPES IN PERU, 2020 - 2023 - Calapuja Suaña, Yeraldine (2024)
The current article aims to analyze the post-pandemic economic recovery through the collection of Income Tax in micro and small enterprises (MYPEs) in Peru between the periods of 2020 and 2023, using statistical data from governmental sources such as SUNAT and BCRP. The SARS-COV-2 negatively impacted the Peruvian economy, reducing GDP by 11.1%, resulting in losses of at least 131 billion soles in 2020. The results indicate that in 2020, tax collection decreased by 20.63% compared to 2019 due to measures taken during the health crisis, but increased by 36.29% in 2021 due to fiscal policies and easing of restrictions. In 2022, recovery continued with a growth of 19.65%, while in 2023 it stabilized with an increase of 0.90%. These data confirm the gradual economic recovery in MYPEs. Continuous analysis of data is crucial for improving tax management. Future research could focus on tax collection of Income Tax in specific business sectors or expanding the study with more recent data. KEYWORDS: COVID-19, Income Tax Collection, MYPEs, Economy.